PENGARUH PENGETAHUAN AKUNTANSI DAN TINGKAT PENDIDIKAN TERHADAP KINERJA USAHA - hardini ariningrum; afif al ansori (Jurnal Akuntansi dan Keuangan (JAK), 2021)
The aim of this research is to get the influence of accounting knowledge and education level on business performance. The Population in this study were MSMEs in Pasar Rakyat Tani Bandar Lampung. The sample selected using purposive sampling and obtained as many as 135 respondents through a questionnaire. The data analysis method used was the Statistical Package for the Social Science (SPSS) program version 20. The instrument testing included validity and reliability tests. The prerequisite test includes a classic assumption test consisting of normality test, muticollinearity test and heteroscedasticity test as well as hypothesis testing consisting of partial test with t-test. The results of the research get accounting knowledge and the level of education has an effect on business performance. Accounting knowledge has a positive effect on business performance. The level of education has a positive effect on business performance.